Catalytic upgrading of renewable levulinic acid to ethyl levulinate biodiesel using dodecatungstophosphoric acid supported on desilicated H-ZSM-5 as catalyst - Nandiwale, Kakasaheb Y.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Patil, Vilas S.; Bokade, Vijay V. (Applied Catalysis A-General, 2013)
Levulinic acid (LA) is considered as a renewable platform chemical and can be used for the synthesis of variety of important fuels and chemicals. In particular, its esterification with ethanol produces ethyl levulinate (EL) would be green process, as it can be used as diesel miscible biofuel (DMB), preventing global warming by decreasing atmospheric CO2. This study explores the use of modified H-ZSM-5 by desilication viz.; DH-ZSM-5 and dodecatungstophosphoric acid (DTPA) loaded on DH-ZSM-5 for esterification of LA with ethanol aiming to EL. Different degree of desilication of H-ZSM-5 was performed by using aq. NaOH (0.2-1.5 M) at 338 K for 30 min and then DTPA was loaded on these desilicated H-ZSM-5 (DH-ZSM-5) support. H-ZSM-5, DH-ZSM-5 and DTPA on these DH-ZSM-5 samples were characterized by powder x-ray diffraction (XRD), N-2 adsorption-desorption, pyridine chemisorbed IR spectroscopy, Temperature Programmed Ammonia Desorption (TPAD). The increase in conversion of levulinic acid was observed from 28% to 94% with increase of DTPA loading from 0% to 15%. The increased LA conversion may be due to increase in total acidity from 43.14% to 84.31%. The use of DH-ZSM-5 as support for deposition of DTPA may be reported for the first time. The present work also extended to optimize process parameters such as DTPA loading on DH-ZSM-5, catalyst to LA ratio, LA to ethanol molar ratio, speed of agitation, particle size reaction temperature and catalyst reusability. Kinetic study based on pseudo-homogeneous (P-H) model is also presented. The experimental results follow second order kinetics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: desilicated H-ZSM-5; DTPA on desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate